Development of a SNP barcode to genotype Babesia microti infections. - Mary Lynn Baniecki; Jade Moon; Kian Sani; Jacob E Lemieux; Stephen F Schaffner; Pardis C Sabeti (Public Library of Science (PLoS), 2019)
Babesia microti is tick-borne disease that is an emerging threat to public health due to increasing prevalence and expanding geographic range. Detection and constant surveillance of babesiosis is imperative for predicting pathogen expansion. Leveraging our whole genome sequence (WGS) analyses of B. microti, we developed a single nucleotide polymorphism (SNP)-based high resolution melt (HRM) surveillance tool. We developed our HRM assay using available sequence data and identified 775 SNPs. From these candidate SNPs, we developed a 32-SNP barcode that is robust and differentiates geographically distinct populations; it contains SNPs that are putatively neutral, located in nuclear, mitochondrial, and apicoplastal regions. The assays are reproducible and robust, requiring a small quantity of DNA (limit of detection as low as 10 pg.). We analyzed the performance of our HRM assay using 26 B. microti clinical samples used in our WGS study from babesiosis endemic regions in the United States. We identified a minimal barcode consisting of 25 SNPs that differentiate geographically distinct populations across all clinical samples evaluated (average minor allele frequency > 0.22). Supporting our previous WGS findings, our 25-SNP barcode identified distinct barcode signatures that segregate B. microti into two lineages: Northeast and Midwest, with the Northeast having three subpopulations: Connecticut/Rhode Island, Nantucket, and the R1 reference group. Our 25-SNP HRM barcode provides a robust means genetic marker set that will aid in tracking the increasing incidence and expanding geographic range of B. microti infections.